Targeted and Untargeted Proteomics Approaches in Biomarker Development. Issue 9 (30th January 2020) - Sobsey, Constance A.; Ibrahim, Sahar; Richard, Vincent R.; Gaspar, Vanessa; Mitsa, Georgia; Lacasse, Vincent; Zahedi, René P.; Batist, Gerald; Borchers, Christoph H.
Abstract: An enormous amount of research effort has been devoted to biomarker discovery and validation. With the completion of the human genome, proteomics is now playing an increasing role in this search for new and better biomarkers. Here, what leads to successful biomarker development is reviewed and how these features may be applied in the context of proteomic biomarker research is considered. The "fit‐for‐purpose" approach to biomarker development suggests that untargeted proteomic approaches may be better suited for early stages of biomarker discovery, while targeted approaches are preferred for validation and implementation. A systematic screening of published biomarker articles using MS‐based proteomics reveals that while both targeted and untargeted technologies are used in proteomic biomarker development, most researchers do not combine these approaches. i) The reasons for this discrepancy, (ii) how proteomic technologies can overcome technical challenges that seem to limit their translation into the clinic, and (iii) how MS can improve, complement, or replace existing clinically important assays in the future are discussed.